2016
DOI: 10.1186/s13635-016-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

DST approach to enhance audio quality on lost audio packet steganography

Abstract: Lost audio packet steganography (LACK) is a steganography technique established on the VoIP network. LACK provides a high-capacity covert channel over VoIP network by artificially delaying and dropping a number of packets in use to convey stegnogram. However, the increasing loss of packets will hurt the quality of the VoIP service. The quality deterioration will not only affect the legitimate VoIP service but also constrain the capacity of the covert channel. Discrete spring transform (DST) is proven to be a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…LACK [1] method, which used the packet loss as an advantage and created space in hidden communication channels by forcing packet loss and introduces redundant frames with secret messages embedded in it. Q i, P e n g and S h a r i f [13] in 2016 worked on the technique LACK proposed by M a z u r c z y k and L u b a c z [1], The original method embedded the secret message by forced loss of VoIP frames and introduced redundant frames with secret message embedded in it. As a result, the number of redundant frames was increased.…”
Section: Packet Loss Methodsmentioning
confidence: 99%
“…LACK [1] method, which used the packet loss as an advantage and created space in hidden communication channels by forcing packet loss and introduces redundant frames with secret messages embedded in it. Q i, P e n g and S h a r i f [13] in 2016 worked on the technique LACK proposed by M a z u r c z y k and L u b a c z [1], The original method embedded the secret message by forced loss of VoIP frames and introduced redundant frames with secret message embedded in it. As a result, the number of redundant frames was increased.…”
Section: Packet Loss Methodsmentioning
confidence: 99%
“…DWT-based speech steganography is introduced in [6]. The discrete spring transform (DST) is used in [39] within a scheme called DST-LACK, which is a speech-in-speech steganography that reduces the effect of packet loss caused by the LACK covert channel scheme [31] to make the latter method less detectable.…”
Section: Related Workmentioning
confidence: 99%
“…In 2016, Qi et al used Discrete Spring Transform to eliminate redundancy in multimedia signals and improve speech quality [18]. Liu et al reported the use of a matrix embedding method to achieve steganography in linear predictive coding for low bit-rate speech codec [19].…”
Section: Related Workmentioning
confidence: 99%